The Effectiveness of Wordwall-Based Interactive Digital Media in Stimulating Language Development in 4- to 5-Year-Old Children - Levi Oga Rostita; Rika Partika Sari; Ranny Fitria Imran (Early Childhood Research and Practice, 2026)
This study aims to examine and analyze the effectiveness of Wordwall-based interactive digital media in stimulating the language development of children aged 4–5 years. The study used a quantitative approach using a quasi-experimental design involving two groups: an experimental group and a control group. The population consisted of 30 children enrolled in Classes A1 and A2 at PAUD Mekar Melati, with 15 children assigned to the control group (A1) and 15 children assigned to the experimental group (A2). The control group received conventional learning instruction using picture cards, while the experimental group was taught using Wordwall-based interactive digital media. Data were collected through pre-test and post-test assessments to measure children's language development before and after the implementation of the treatment. The collected data were analyzed using an Independent Samples t-test following prerequisite tests of normality and homogeneity. The findings revealed a statistically significant difference in language development between children in the experimental group and those in the control group. This result was evidenced by a significance value (Sig. 2-tailed) of 0.028 (< 0.05), indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. Furthermore, the post-test results demonstrated that the mean score of the experimental group was higher than that of the control group. Therefore, it can be concluded that the use of Wordwall-based interactive digital learning media is effective in enhancing the language development of children aged 4–5 years.